2007
DOI: 10.1038/sj.jcbfm.9600580
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Monocyte Infiltration in an Animal Model of Neuroinflammation Using SPIO-Labeled Monocytes or Free USPIO

Abstract: Magnetic resonance imaging (MRI) has been applied to visualize monocyte infiltration with the use of intravenously injected ultrasmall superparamagnetic iron oxide (USPIO). However, USPIO uptake in vivo remains elusive, and the heterogeneous enhancement patterns observed by MRI point to multiple pathophysiological events. This study focused on specific imaging of monocyte infiltration into the brain by transfusion of superparamagnetic iron oxide (SPIO)-labeled monocytes in a rat model of neuroinflammation, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…In small animal models of MS (experimental autoimmune encephalomyelitis (EAE)), SPIO can be used to image macrophage activity [177] and infiltration [178], lymphocyte infiltration (CD3 + cells [179]) and the labeling of T-cells [180]. Also in the case of heart attack, numerous studies show that SPIO can image the accompanying neuroinflammation or the macrophage activity [181] and macrophage migration [182] similarly to the changes in MS. Moreover, it was able to be shown that early stages of post-radiogenic brain damage can be imaged via targeted SPIO-AB against ICAM-1 [183].…”
Section: Imaging Of Multiple Sclerosis (Ms) and Neurodegenerationmentioning
confidence: 99%
“…In small animal models of MS (experimental autoimmune encephalomyelitis (EAE)), SPIO can be used to image macrophage activity [177] and infiltration [178], lymphocyte infiltration (CD3 + cells [179]) and the labeling of T-cells [180]. Also in the case of heart attack, numerous studies show that SPIO can image the accompanying neuroinflammation or the macrophage activity [181] and macrophage migration [182] similarly to the changes in MS. Moreover, it was able to be shown that early stages of post-radiogenic brain damage can be imaged via targeted SPIO-AB against ICAM-1 [183].…”
Section: Imaging Of Multiple Sclerosis (Ms) and Neurodegenerationmentioning
confidence: 99%
“…To date, the majority of studies using ex vivo labeling in stroke models addressed cellular therapy, using subventricular zone progenitor cells (Athiraman et al, 2009;Cicchetti et al, 2007;Jiang et al, 2005;Zhang et al, 2003), embryonic neural stem cells (Hoehn et al, 2002;Modo et al, 2004) mesenchymal stem cells (Lee et al, 2009;Walczak et al, 2008), spleenderived mononuclear cells (Stroh et al, 2006) or adipose-derived stem cells (Rice et al, 2007). To our knowledge, only one study was published using ex vivo labeling of macrophages in a rat stroke model (Engberink et al, 2008): 4 rats were intravenously injected with 5 million SPIO-labeled monocytes after induction of cerebral ischemia by photothrombosis. MRI was performed at 4.7T pre-and 24h, 72h and 120h post-injection.…”
Section: Ex Vivo Labeling Of Phagocytic Cellsmentioning
confidence: 99%
“…At later time-points, these hyposignals were detected in the lesion core (Kleinschnitz et al, 2003). The hypothesis of passive diffusion of iron oxide nanoparticles through a disrupted blood brain barrier (BBB) was rejected, because post-gadolinium and post-(U)SPIO MR signal changes did not superimpose, suggesting an active mechanism of brain entry, via (U)SPIO-laden infiltrating macrophages (Engberink et al, 2008;Kleinschnitz et al, 2003). Table 1.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations